Recurrence of nasopharyngeal carcinoma in the mastoid region: Therapeutic approach of a rare clinical entity [Nazofarenks kanserinin mastoid bölge rekürrensi: Nadir bir klinik tablonun tedavisi] - (:unkn) unknown (Marmara University, 2014)
Mastoid region recurrence is a rare entity for nasopharyngeal cancer. This paper presents a patient with an isolated mastoid recurrence following definitive treatment and discusses the therapeutic approach which may help in the treatment of such cases. © 2014, Marmara University. All rights reserved.
Keywords: Chemotherapy; Mastoid region recurrence; Nasopharyngeal carcinoma; Radiotherapy